Diagnostic performance of ultrasonographic medial gastrocnemius muscle thickness for sarcopenia in patients on maintenance hemodialysis - Meilin Yan; Wei An; Leting Zhou; Weiwei Shan; Xiran Zhang; Aiyan Du; Zhijian Zhang; Liang Wang (Frontiers in Medicine, 2026)
Objective The study aimed to evaluate the performance of ultrasonographic medial gastrocnemius muscle thickness (MGMT) and pennation angle (MGMPA) in diagnosing sarcopenia among patients on maintenance hemodialysis (MHD). Methods The MGMT and MGMPA were measured ultrasonographically. Baseline characteristics were compared between the sarcopenia and non-sarcopenia groups. Correlations between ultrasound parameters and sarcopenia indicators were evaluated. The diagnostic performance of the ultrasound parameters was assessed using receiver operating characteristic (ROC) curve analysis. Multivariable logistic regression analysis was conducted to identify independent predictors associated with sarcopenia, followed by the construction and validation of a diagnostic nomogram. Additionally, bootstrap mediation analysis assessed the direct and indirect effects of sonographic parameters on sarcopenia. Results This study cohort comprised 221 MHD patients. Both MGMT (12.8 vs. 16.5 mm, p < 0.001) and MGMPA (26.35° vs. 29.73°, p < 0.001) were significantly reduced in the sarcopenia group compared to the non-sarcopenia group. MGMT exhibited significant positive correlations with calf circumference, appendicular skeletal muscle mass index (ASMI), appendicular skeletal muscle mass (ASM), body mass index (BMI), and handgrip strength, alongside a significant inverse correlation with the SARC-CalF score. MGMT demonstrated good diagnostic performance for sarcopenia, yielding an area under the curve (AUC) of 0.823 ( p < 0.001). Multivariable logistic regression identified MGMT, BMI, older age, and male gender as independent predictors of sarcopenia. A predictive nomogram incorporating these factors demonstrated excellent discrimination (AUC = 0.873), good calibration, and potential clinical decision-making value across a wide threshold probability range. Mediation analysis confirmed a significant direct association between MGMT and the presence of sarcopenia in both the age model (ADE = −0.00303, p < 0.001) and the serum albumin model (ADE = −0.00251, p < 0.001), with no significant mediating effects observed for either variable. Conclusion Ultrasonographic measurement of MGMT demonstrates high diagnostic performance and serves as a reliable, independent predictor for sarcopenia in patients undergoing maintenance hemodialysis, highlighting its potential as a practical, non-invasive screening tool in clinical practice.